2012
DOI: 10.1111/iej.12019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tooth isolation on laser Doppler readings

Abstract: Pulpal blood flow measurements could be obtained with multiple teeth isolation and single tooth isolation. Multiple teeth isolation blocked signal contamination better. Single tooth isolation provided significantly different readings for regular blood flow and LI conditions and may therefore provide an option for pulpal blood flow assessment with LDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
1
5
0
2
Order By: Relevance
“…In our study, the PBF levels of the traumatised teeth were approximately 25 AU (26.32 ± 17.14), which were similar to the results reported by Setzer et al and Todea et al [23,24]. In the period immediately after the trauma, changes in the vascularization of the pulp tissues and its dynamics have occurred due to the injury, resulting in a statistically significant increase in the PBF levels of the affected teeth in the test group compared to those in the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, the PBF levels of the traumatised teeth were approximately 25 AU (26.32 ± 17.14), which were similar to the results reported by Setzer et al and Todea et al [23,24]. In the period immediately after the trauma, changes in the vascularization of the pulp tissues and its dynamics have occurred due to the injury, resulting in a statistically significant increase in the PBF levels of the affected teeth in the test group compared to those in the control group.…”
Section: Discussionsupporting
confidence: 92%
“…In this context, results of studies conducted by Akpinar et al, Gopikrishna et al and Polat et al have reported false-positive outcomes due to the interference of laser transmission in case of discoloration of the tooth crown or contamination of the backscattered light from the periodontal tissues [ 26 , 27 , 28 ]. The following factors have a great impact on the accuracy of the LDF values: the probe design and its position, single or multiple isolated teeth and the mineral contents of the inspected hard dental tissues [ 14 , 23 , 26 ]. Hence, future studies need to investigate the implementation of a new non-invasive technology, as a diagnostic tool of traumatised teeth.…”
Section: Discussionmentioning
confidence: 99%
“…The position of drilling corresponding to the test teeth in the impression was situated in the middle of the tooth surface and distanced from the gingival margin about 3-5mm [20], and the diameter of the drilling hole was consistent with the probe. The subjects were asked to keep in the seated, calm and relaxed state after the LDF was preheated and calibrated, and then the silicone rubber impression was reset to the detected area in the test area (Fig 1[21]).…”
Section: Pbf Data Acquisitionmentioning
confidence: 99%
“…Assim, o teste pulpar elétrico é importante. A Fluxometria Laser Doppler e a oximetria de pulso são métodos fisiométricos de verificação vascular, detectando vitalidade em dentes traumatizados antes que testes comuns (SETZER FC, et al, 2013).…”
Section: Introductionunclassified